2016
DOI: 10.1177/1359105314564019
|View full text |Cite
|
Sign up to set email alerts
|

Coming out during adolescence: Perceived parents’ reactions and internalized sexual stigma

Abstract: Disclosing sexual orientation to parents is a challenging developmental task for lesbian and gay adolescents. The aim of the study is to investigate parental negative reaction to coming out, which is associated with high levels of internalized sexual stigma and psychological problems. Participants' perceptions of their parents' reactions, age at coming out, gender, parental political orientation and religiosity, family functioning, and internalized sexual stigma were assessed in 150 Italian homosexual adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 26 publications
1
43
0
2
Order By: Relevance
“…As reported for other stigmatized identities (Weisz et al, 2015), higher levels of outness may boost the health benefits of social support in gay men and transgender women, living or not with HIV. Acceptance by significant others, such as family and friends—after sharing an HIV diagnosis or revealing one’s true self—allows people to recapture a feeling of self-confidence and control over their lives and therefore, to continue with personal projects and goals (Baiocco et al, 2014). As known, human beings need to be accepted by others, belong to a group, and have affectionate and pleasant exchanges with other people in a context of stability (Baumeister and Leary, 1995; Williams, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As reported for other stigmatized identities (Weisz et al, 2015), higher levels of outness may boost the health benefits of social support in gay men and transgender women, living or not with HIV. Acceptance by significant others, such as family and friends—after sharing an HIV diagnosis or revealing one’s true self—allows people to recapture a feeling of self-confidence and control over their lives and therefore, to continue with personal projects and goals (Baiocco et al, 2014). As known, human beings need to be accepted by others, belong to a group, and have affectionate and pleasant exchanges with other people in a context of stability (Baumeister and Leary, 1995; Williams, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, cis-heterosexism and cis-heteronormativity is pervasive at an institutional level, and LGBQ+ people face stigma and prejudice in several contexts (Baiocco and Pistella, 2019;Rollè et al, 2020). Previous research has identified the family, school, and healthcare arenas as potentially negative environments for Italian sexual minorities (Baiocco et al, 2015(Baiocco et al, , 2020Rosati et al, 2020), and other research has highlighted the relationship between ISS and CO (Baiocco et al, 2016;Pistella et al, 2020b). As mentioned above, another environment potentially causing minority stress for Italian sexual minorities is represented by the Catholic Church: a recent study (Garelli, 2013) estimated that approximately 80% of Italian citizens identify as Catholic, thus for sure including also a share of the Italian LGBQ+ population.…”
Section: Present Studymentioning
confidence: 99%
“…Raziskava, ki sta jo izvedla Švab in Kuhar (2005), kaže, da se homoseksualci res najprej razkrijejo prijateljem, ker lahko predvidevajo njihovo reakcijo, medtem ko je razkritje v družinskem okolju nekoliko težje in bolj čustveno. Reakcije staršev so različne ter odvisne od splošnih odnosov v družini, povezanosti med družinskimi člani, stopnje religioznosti ter stopnje upoštevanja tradicionalnih vzorcev (Švab & Kuhar, 2005;Baiocco, et al, 2016).…”
Section: Diskusijaunclassified